Quality of life in South East Asian patients who consult for dyspepsia: validation of the short form Nepean Dyspepsia Index. - Mahadeva, S.; Wee, H.; Goh, K.; Thumboo, J. (2009)
This study demonstrates that both English and Malay versions of the SF-NDI are reliable and probably valid instruments for measuring HRQoL in Malaysian patients with dyspepsia.